The feasibility of a randomised control trial to assess physiotherapy against surgery for recurrent patellar instability. - Gemperle-Mannion, E; Qureshi, A; Edwin, C; Smith, TO; Parsons, H; Mason, J; Underwood, M; Eldridge, J; Thompson, P; Metcalfe, A; PIPS study team (BioMed Central, 2020)
Background:Patellar instability is a relatively common condition that leads to disability and restriction of activities. People with recurrent instability may be given the option of physiotherapy or surgery though this is largely driven by clinician preference rather than by a strong evidence base. We sought to determine the feasibility of conducting a definitive trial comparing physiotherapy with surgical treatment for people with recurrent patellar instability. Methods:This was a pragmatic, open-label, two-arm feasibility randomised control trial (RCT) with an embedded interview component recruiting across three NHS sites comparing surgical treatment to a package of best conservative care; 'Personalised Knee Therapy' (PKT). The primary feasibility outcome was the recruitment rate per centre (expected rate 1 to 1.5 participants recruited each month). Secondary outcomes included the rate of follow-up (over 80% expected at 12 months) and a series of participant-reported outcomes taken at 3, 6 and 12 months following randomisation, including the Norwich Patellar Instability Score (NPIS), the Kujala Patellofemoral Disorder Score (KPDS), EuroQol-5D-5L, self-reported global assessment of change, satisfaction at each time point and resources use. Results:We recruited 19 participants. Of these, 18 participants (95%) were followed-up at 12 months and 1 (5%) withdrew. One centre recruited at just over one case per month, one centre was unable to recruit, and one centre recruited at over one case per month after a change in participant screening approach. Ten participants were allocated into the PKT arm, with nine to the surgical arm. Mean Norwich Patellar Instability Score improved from 40.6 (standard deviation 22.1) to 28.2 (SD 25.4) from baseline to 12 months. Conclusion:This feasibility trial identified a number of challenges and required a series of changes to ensure adequate recruitment and follow-up. These changes helped achieve a sufficient recruitment and follow-up rate. The revised trial design is feasible to be conducted as a definitive trial to answer this important clinical question for people with chronic patellar instability. Trial registration:The trial was prospectively registered on the International Standard Randomised Controlled Trial Number registry on the 22/12/2016 (reference number: ISRCTN14950321). http://www.isrctn.com/ISRCTN14950321.